Regional Development Through Tourist Destinations in Tanjungbalai City - Amalia, Fiqrida; Rivai, Ahmad (Publisher Cv. Inara, 2022)
Regional development is a basic idea and effort in allocating and managing the resources owned for the interests and progress of a region. The development of an area can be done through the development of tourist destinations in an area. This study aims to describe regional development through tourist destinations in Tanjungbalai City. This research uses qualitative research with descriptive method. The research was conducted in several stages: (a) field surveys on tourist destinations, (b) preparation of research instruments, (c) data collection, (d) data processing and analysis, (e) preparation and reporting of research results. The research findings show that regional development through tourist destinations in Tanjungbalai City has also met the criteria, including: Something to see, Something to do, and Something to buy. The development of tourist destinations in this city is also supported by the availability of adequate accommodation and accessibility facilities. The existence of various tourist objects and destinations in Tanjungbalai City also has a socio-economic impact for the community around the tourist attraction locations and helps reduce unemployment in Tanjungbalai City.